Mechanical countermeasures for spaceflight-associated neuro-ocular syndrome during 30-days of head down tilt bed rest: design, implementation, and tolerability - Moestl, Stefan; De Boni, Laura; Hoenemann, Jan-Niklas; Kramer, Tilmann; Schmitz, Jan; Pesta, Dominik; Frett, Timo; Bohmeier, Maria; Frings-Meuthen, Petra; Ewald, Ann Charlotte; Nitsche, Andrea; Loehr, Patricia; et al. (Frontiers in Physiology, 2025)
After longer duration space missions, some astronauts experience structural and functional changes in the eye and structural changes in the brain, termed Spaceflight-Associated Neuro-Ocular Syndrome (SANS). Countermeasures against SANS are required to minimize potential operation impacts and negative long-term health consequences. Headward fluid shifts, which appear to promote SANS, provide a target for countermeasures. The SANS countermeasures study, a 30 days strict head down tilt bed rest (HDTBR) study, tested two mechanical countermeasures aimed at reversing cephalad fluid overload. This work presents design and methodology of the study with a focus on countermeasure implementation and tolerability. Following baseline evaluations, participants were randomized to four groups and HDTBR commenced: Daily application of 25 mmHg lower body negative pressure for 6 h, six-hour bilateral venous constrictive thigh cuffs following moderate cycling exercise on 6 days per week, a negative control group without countermeasures, and a positive control group with HDTBR interruption for 6 h per day by sitting upright. The potential of these countermeasures for future space applications was examined in 86 different experiments, which will be reported elsewhere. Comfort ratings ranging from 1 (very uncomfortable) to 5 (very comfortable) were used to asses tolerability. Overall, 47 participants (20 women) completed the study. Out of 4,032 h scheduled for both countermeasures, 10.5 h were not performed due to medical issues unrelated to the countermeasures. Mean comfort ratings were 3.9 in men and 4.4 in women in the lower body negative pressure group (p = 0.1356) and 4.2 in men and 3.9 in women in the thigh cuff group (p = 0.1604). We conclude that both countermeasures were well tolerated and applied under well controlled conditions, thus, allowing for meaningful analyses of efficacy in attenuating HDTBR effects.